Agile Transformation in Banking & Allied Services - Miranda, Marilyn (Digital Repository of Theses, 2024)
The Agile methodology is a project management approach that involves breaking the project into phases and emphasizes continuous collaboration and improvement. This set of techniques, values and principles are designed to guide and improve how software development teams work together to deliver new applications and updates. The aim of the study is to elaborate on areas that help maximize the benefits of improving advocacy and acceptance of Agile methods creating the desired amount of impact on people and products. Flexibility to change and adapt during the development cycle is the core selling point allowing teams to create higher quality products keeping in mind customer needs. This is in comparison to earlier methods used like Waterfall where progression has gradually happened keeping in mind advancements in various fields of work, which not only has improved the agility and speed required for project related changes but also accelerated the pace in a data driven environment. Methodology used for this dissertation was through case studies, focus group surveys and semi-structured interviews. Qualitative study on the concepts of Agile in day to day management of organizations using tools and methodologies available and thrives on metrics like burndown charts and control graphs to help the team predict their delivery cadence. Main results achieved were that using the Agile approach of continuous review and short design time-frame, the project team is better adapted to mobilize projects in tune with rapidly evolving environments in which the system will be used. Each initiative in the roadmap breaks down into a set of requirements which remain lean where everyone on the team develops a shared understanding via ongoing conversation and collaboration which is fleshed out into full details during implementation. We learn and improve performances to become Lean through experiments and breakdowns. Process improvements are achieved by reducing variation through these experiments and through acting on the root causes of breakdowns. In conclusion, Agile is not a destination – it’s a path towards changing how your organization defines roles, plans accountability and mechanisms for responding to market changes This paper fills the gap in the digital library management literature by providing an overview of Agile Project Management versus and the pressing need for this being a core requirement due to the ever changing dynamic scenario driven by technology upgrade and competition. In this paper we discussed how Agile empowers teams, builds accountability, encourages innovation while promoting continuous improvement in banking and allied services. More work is needed to understand a) How can projects be described across domains in a consistent manner ? b) How projects across domains can leverage the stored intellect and insights interchangeably? c) What guidance can be provided to create and sustain better agile behavior to ensure successful outcomes ? The hope is that as researchers start to address these questions in their research designs so that others easily leverage and apply the research results.